The Effect Of Inflation On The Financial Center Of Syrian Traditional Banks Using The VECM Model - الحايك باسل; منصور يمن; سليمان طلال (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Inflation is considered one of the most important measures that express the economic situation in a particular country in terms of social, economic and financial prosperity, as the high fluctuation in this measure leads to weak citizens’ confidence in the local currency and low real value of savings and deposits, and also leads to confusion in the local market movement, due to concerns Exporters and importers are unable to conduct business deals due to the high risk margin resulting from this volatility This research aims to study the rate of inflation during the period between 1/1/2009 until December 31, 2018, and the mechanism of its impact on the financial position of the traditional Syrian banks. The study showed that the rate of inflation during the studied period affects the financial position of traditional banks, and this effect is directed only in one direction, which is negative and significant, as an increase in inflation by one Syrian pound leads to an increase in the financial position by 12178860 Syrian pound. Any short-term change in the rate of inflation must affect the model and push it towards equilibrium in the long term, with an adjustment speed of 95.3% during one time period (i.e. a month), meaning that the model returns to stability within a period of one month and two days.